Determination of Uranium Concentrations in Some Plants and Soils Samples from Baghdad-Iraq Using CN-85 Track Detector - Essam M.R. Drweesh; Lutfi M. M. Salih; Roaa T. Abdulla (Journal of Madenat Alelem University College, 2012)
The aim of this study is to measure the concentrations of uranium in17 samples of plants and soils collected from different areas in Baghdad city. The technique is based on the counting of α–particles by using the CN-85 track detector that is one of solid state nuclear track detectors (SSNTDs) and fission fragment track technique. The nuclear reaction used as source of uranium fission fragment is U-235 (n-f) obtained by the bombardment of U-235 with thermal neutrons emitted from Am-Be neutron source with thermal neutron flux of 5000 n/cm2.s for seven days. The concentration of uranium was calculated by comparison with the standard samples. The concentrations of uranium in plants sample ranged between 0.8 and 2.37 ppm with average of 1.59 ppm. The concentrations of uranium in soils samples ranged between 3.67 and 3.99 ppm with average of 3.82 ppm.